2017
DOI: 10.1039/c6ta09052d
|View full text |Cite
|
Sign up to set email alerts
|

N-Carbon coated P-W2C composite as efficient electrocatalyst for hydrogen evolution reactions over the whole pH range

Abstract: A N-carbon coated P-modified W2C composite (P-W2C@NC), prepared by annealing a mixture of H3PW12O40and dicyandiamide, exhibits excellent HER electrocatalytic activity and durability over the whole pH range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(103 citation statements)
references
References 48 publications
6
94
0
3
Order By: Relevance
“…Notably, the N 1s peak of the Carbon‐PMo 12 composite (Figure e) can be divided into three peaks at 402.7, 400.8, and 398.5 eV, which correspond to graphitic‐N, pyrrolic‐N, and pyridinic‐N species, respectively . The C 1s peaks of the Carbon‐PMo 12 located at 289.1, 285.8, and 284.8 eV (Figure S3) were characteristic of C−N, C=N, and C−C/C=C, respectively . Compared with PMo 12 , the Mo peak of the Carbon‐PMo 12 shifted toward lower binding energy, suggesting electrostatic interactions between the PMo 12 clusters and carbon substrate …”
Section: Resultsmentioning
confidence: 98%
“…Notably, the N 1s peak of the Carbon‐PMo 12 composite (Figure e) can be divided into three peaks at 402.7, 400.8, and 398.5 eV, which correspond to graphitic‐N, pyrrolic‐N, and pyridinic‐N species, respectively . The C 1s peaks of the Carbon‐PMo 12 located at 289.1, 285.8, and 284.8 eV (Figure S3) were characteristic of C−N, C=N, and C−C/C=C, respectively . Compared with PMo 12 , the Mo peak of the Carbon‐PMo 12 shifted toward lower binding energy, suggesting electrostatic interactions between the PMo 12 clusters and carbon substrate …”
Section: Resultsmentioning
confidence: 98%
“…Because the impedance data of other catalysts also fit in the equivalent circuit, the smaller the R ct , the better the electrical conductivity, and hence the better the HER performance. It can be seen that Co 2 P@N,P‐C/CG had the smallest R ct of 2.54 Ω among all catalysts (at 0.1 V vs. RHE), which may be because 1) the introduction of RGO could improve the conductivity, 2) the N,P‐dopants improve the graphitization degree of the carbon materials, 3) the Co 2 P exhibits metallic properties with a higher conductivity, or 4) the C shell can enhance interfacial electron transfer in the morphology of Co 2 P cores and a C shell . Recently, some reports have suggested that the Tafel slope derived from the polarization curve may contain the contribution of the electron transport process, whereas the Tafel slopes obtained from the impedance data can completely consider the charge transfer kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…[53][54][55][56] POMs can not only give rise to an assembly of catalytically active metal and nonmetal elements into one nanoscale cluster,b ut they can also be easily dispersed in variousc arbon sourceso wing to their high negative charge, whichi sb eneficial for uniform carbonization, phosphorization,o rn itrogenization in confined spaces. In the last three years, as eries of transition-metal carbides, nitrides, and phosphides have been prepared by using POM precursors, [57][58][59][60][61][62] suggesting af easible strategyf or the construction of nano-heterojunctions. Herein, we report an ew type of nano-heterojunction that consists of cobalt phosphide and tungsten carbide composite phases covered by few-layer N-doped graphitic carbon shells (Co 2 P/ WC@NC).…”
Section: Introductionmentioning
confidence: 99%